1992
DOI: 10.1073/pnas.89.15.7247
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester-induced amino-terminal phosphorylation of human JUN but not JUNB regulates transcriptional activation.

Abstract: Phorbol ester tumor promoters activate gene transcription by regulating both the synthesis and posttranslational modification of the activator protein 1 (AP-1) transcription factor. c-Jun and JunB are components of the mammalian AP-1 complex. Here we demonstrate that in U-937 human leukemic cells, phorbol esters stimulate the phosphorylation of the amino terminus of human c-Jun (JUN) but not human JunB (JUNB). Mutational analysis indicates that serine-63 and -73, which reside within the putative regulatory dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 30 publications
4
57
1
Order By: Relevance
“…Increased transcriptional activity of c-Jun has been ascribed to phosphorylation of residues 63 and 73 in the transactivation domain of this DNAbinding factor and prevailing evidence suggest that this is achieved through the JNKs rather than the ERKs (Hibi et al, 1993;Minden et al, 1994b). Interestingly, in a previous study, it was reported that PMA stimulates the phosphorylation of these serine residues (Wasylyk et al, 1994;Franklin et al, 1992). However, in those studies the authors concluded that the phosphorylation of c-Jun was due to ERK1 and ERK2 (Pulverer et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Increased transcriptional activity of c-Jun has been ascribed to phosphorylation of residues 63 and 73 in the transactivation domain of this DNAbinding factor and prevailing evidence suggest that this is achieved through the JNKs rather than the ERKs (Hibi et al, 1993;Minden et al, 1994b). Interestingly, in a previous study, it was reported that PMA stimulates the phosphorylation of these serine residues (Wasylyk et al, 1994;Franklin et al, 1992). However, in those studies the authors concluded that the phosphorylation of c-Jun was due to ERK1 and ERK2 (Pulverer et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…TPA significantly increases the Nterminal phosphorylation, resulting in a robust induction of cJun transactivation activity Lin et al, 1992;Smeal et al, 1992;Nikolakaki et al, 1993). In contrast, Jun B, lacking serine-63 and-73, is irresponsive to TPA induced transcriptional activation (Franklin et al, 1992).…”
Section: C-jun Expression and Activitymentioning
confidence: 99%
“…The resulting expression vector contained a hygromycin B-selectable marker and was driven by the human IIa metallothionein (hMTIIa) promoter. GST-cJun(5-89) and GAL4-cJun(5-89) have been described previously (19,25,26). pCMV-FLAG-p38 MAPK (7) was provided by R. Davis.…”
Section: Methodsmentioning
confidence: 99%
“…Transient transfections were performed using the DEAE-dextran procedure as described previously (32). Stable transfections were performed by electroporation (26). Two days post-transfection, cells were cultured in selective media containing 200 g/ml hygromycin B (Calbiochem).…”
Section: Methodsmentioning
confidence: 99%